Effects of agonist-antagonist complex resistance training on upper body strength and power development - Robbins, D. W.; Young, W. B.; Behm, D. G.; Payne, W. R. (Journal of Sports Sciences, 2009)
he objective of this study was to examine the chronic effects on strength and power of performing complex versus traditional set training over eight weeks. Fifteen trained males were assessed for throw height, peak velocity, and peak power in the bench press throw and one-repetition maximum (1-RM) in the bench press and bench pull exercises, before and after the eight-week programme. The traditional set group performed the pulling before the pushing exercise sets, whereas the complex set group alternated pulling and pushing sets. The complex set training sessions were completed in approximately half the time. Electromyographic (EMG) activity was monitored during both test sessions in an attempt to determine if it was affected as a result of the training programme. Although there were no differences in the dependent variables between the two conditions, bench pull and bench press 1-RM increased significantly under the complex set condition and peak power increased significantly under the traditional set condition. Effect size statistics suggested that the complex set was more time-efficient than the traditional set condition with respect to development of 1-RM bench pull and bench press, peak velocity and peak power. The EMG activity was not affected. Complex set training would appear to be an effective method of exercise with respect to efficiency and strength development.